2018
DOI: 10.1111/cei.13124
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of single nucleotide polymorphisms in the interleukin-6 receptor and their effects on pre- and post-transplant serum mediator level and outcome after allogeneic stem cell transplantation

Abstract: Interleukin (IL)-6 is an important regulator of immunity and inflammation in many diseases. Single nucleotide polymorphisms (SNPs) in the IL-6 gene influence outcome after allogeneic stem cell transplantation (ASCT), but the possible importance of SNPs in the IL-6 receptor has not been examined. We therefore investigated whether SNPs in the IL-6R gene influenced biochemical characteristics and clinical outcomes after ASCT. We examined the IL-6 promoter variant rs1800975 and the IL-6R SNPs rs4453032, rs2228145,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…We observed that patients with the IL6-174 GG genotype developed acute GVHD (grade II–IV) more frequently than individuals with the C allele. While our data are in agreement with most previous studies which suggest a relationship between the IL6-174 GG genotype of the recipients and an increased risk for development of acute GVHD (Ambruzova et al 2009 ; Cavet et al 2001 ; Dickinson and Charron 2005 ; Dukat-Mazurek et al 2017 ), other authors did not observe an association between IL6-174 SNP and acute GVHD (Lin et al 2003 ; Mullighan et al 2004 ; Tvedt et al 2018 ). To our knowledge, only one study focused on a detailed analysis of the impact of IL6-597 SNP on the outcome of allogeneic HSCT.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that patients with the IL6-174 GG genotype developed acute GVHD (grade II–IV) more frequently than individuals with the C allele. While our data are in agreement with most previous studies which suggest a relationship between the IL6-174 GG genotype of the recipients and an increased risk for development of acute GVHD (Ambruzova et al 2009 ; Cavet et al 2001 ; Dickinson and Charron 2005 ; Dukat-Mazurek et al 2017 ), other authors did not observe an association between IL6-174 SNP and acute GVHD (Lin et al 2003 ; Mullighan et al 2004 ; Tvedt et al 2018 ). To our knowledge, only one study focused on a detailed analysis of the impact of IL6-597 SNP on the outcome of allogeneic HSCT.…”
Section: Discussionsupporting
confidence: 93%
“…We did not find any significant relationships between OS, EFS, RI, TRM and the IL6-174 and IL6-597 polymorphisms of recipient and donor. Ambruzova et al (2009) and Tvedt et al (2018) described an association between the IL6-174 polymorphism and TRM. Ambruzova et al (2009) and Balavarca et al (2015) observed a relationship between OS and IL6-174 G allele.…”
Section: Discussionmentioning
confidence: 99%
“…The candidate biomarker of our study was IL6, a cytokine associated with several inflammatory diseases, and a modulator of the immune responses involved in aGvHD pathogenesis (12, 3436). IL6 can be targeted with a selected inhibitory strategy based on anti-IL6 receptor antibody (10), tocilizumab (TCZ).…”
Section: Discussionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) of cytokine or cytokine receptor genes that seem to influence posttransplant outcome include IL-10 promoter gene polymorphisms, TNFd4, TNFα-1031C, IL-6 promoter variants, IL-6 receptor SNPs, CCL5-28CG, CCR9-926AG, IL-23 receptor 1142 GA, and IL-7 receptor α 1237AG [5,6]. They influence both acute and chronic GVHD (severity and organ involvement) as well as susceptibility to infections.…”
Section: Premobilization Factors Contributing To Donor Heterogeneity:mentioning
confidence: 99%